2022
DOI: 10.1038/s41598-022-06393-3
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging spectroscopy for rapid, primary screening of SARS-CoV-2: a proof of concept

Abstract: Effective testing is essential to control the coronavirus disease 2019 (COVID-19) transmission. Here we report a-proof-of-concept study on hyperspectral image analysis in the visible and near-infrared range for primary screening at the point-of-care of SARS-CoV-2. We apply spectral feature descriptors, partial least square-discriminant analysis, and artificial intelligence to extract information from optical diffuse reflectance measurements from 5 µL fluid samples at pixel, droplet, and patient levels. We disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Coronavirus disease (COVID-19) outbreaks in several communities have compelled governments worldwide to enact stringent controls such as blockades, border closures, and widespread screening [ 43 ]. The SARS-CoV-2 virus is compatible with the coronavirus family with single-stranded gene RNA and surface proteins such as membranes, envelopes, nucleocapsids, and spikes [ 44 ].…”
Section: Sars-cov-2 Biosensorsmentioning
confidence: 99%
“…Coronavirus disease (COVID-19) outbreaks in several communities have compelled governments worldwide to enact stringent controls such as blockades, border closures, and widespread screening [ 43 ]. The SARS-CoV-2 virus is compatible with the coronavirus family with single-stranded gene RNA and surface proteins such as membranes, envelopes, nucleocapsids, and spikes [ 44 ].…”
Section: Sars-cov-2 Biosensorsmentioning
confidence: 99%
“…Gomez-Gonzalez et al [ 38 ] reported a proof of concept of optical imaging spectroscopy for rapid, primary screening of SARS-CoV-2. A study by Shah et al [ 39 ] found that home pulse oximetry monitoring identified the need for hospitalization in initially non-severe COVID-19 patients when a cutoff SpO 2 of 92% was used and that home SpO 2 monitoring also reduced unnecessary emergency department revisits.…”
Section: Role Of 18-fluorodeoxyglucose Positron Emission Tomographymentioning
confidence: 99%
“…They range from the detection of the Zika virus in mosquitoes fed with infected human blood using infra-red spectroscopy [29] to the detection of hepatitis B and C viruses [30] and Dengue [31] in human samples using Raman and fluorescence spectroscopy. Most recent efforts aim to detect SARS-CoV-2 models [32] and the SARS-CoV-2 virus [33] , [34] , [35] , [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Several quantitative descriptors based on the measured polarimetric features are defined, calculated at the per-pixel level and later integrated at the per-sample level. This is the same procedure employed by authors for the analysis of hyperspectral images of the same type of samples which allowed for detecting and characterizing those ones with viral content in similar concentrations [ 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%